All-optical switching based on plasmon-induced Enhancement of Index of Refraction - Rakesh Dhama; Ali Panahpour; Tuomas Pihlava; Dipa Ghindani; Humeyra Caglayan (Nature Communications, 2022)
Atomic systems show enhancement of index of refraction and its extension to optical system can be useful for all-optical switching. Here the authors demonstrate coherently controlled plasmon-induced enhancement of index of refraction in L-shaped metasurface.